Satellite-Derived Trends in Inundation Frequency Reveal the Fate of Saltmarshes - Laengner, Marieke Liesa; van der Wal, Daphne (Frontiers in Marine Science, 2022)
Some of the world’s coastal saltmarshes experience loss in area due to environmental changes, such as relative sea level rise and limited sediment supply. We use satellite remote sensing to assess changes in inundation (flooding) frequency in tidal basins and investigate the bio-physical interactions with saltmarshes. We apply a simple automated method to retrieve time series of inundation frequency change and seaward habitat change of saltmarshes and tidal flats from Landsat-5 TM satellite imagery between 1985 and 2011, for a number of contrasting tidal basins (estuaries, deltas) globally. We evaluated the satellite-derived information on inundation frequency with such information obtained from elevation and tide gauge data for the Western Scheldt estuary, showing good agreement. Application of the method on all study sites reveal which tidal basins are stable or net emerging and which tidal basins are net drowning, but also show large spatial variation in the changes in inundation frequency within each basin. Tidal basins experiencing an overall significant increase in inundation frequency (Mississippi Delta and Venice Lagoon) were associated with an overall loss of saltmarsh area. Satellite-derived temporal and spatial information on inundation frequency helps to assess the fate of saltmarshes in light of sea level change, changes in sediment supply and subsidence.